The Role of Islamic Accounting Information Systems in Enhancing Financial Accountability and Transparency - Ratih Pratiwi; Muchtim Humaidi (Universitas Pekalongan, 2026)
This study discusses Islamic Accounting Information Systems in Islamic institutions in Indonesia. The use of accounting systems is considered important because organizations need financial accountability and transparency. The study uses quantitative methods by distributing questionnaires to several employees working in Islamic institutions. The collected data were analyzed using structural equation modeling. The results show that Islamic Accounting Information Systems have an influence on financial accountability and organizational transparency. The system helps organizations prepare financial reports and improve internal control. In addition, user competence also affects the implementation of the system. Employees who understand accounting systems can support organizational activities better. This study also explains that accounting information systems are useful for Islamic institutions because they help organizations manage financial information. The study contributes to the development of accounting information system literature and provides information related to Islamic governance practices